2022
DOI: 10.1177/03611981221083920
|View full text |Cite
|
Sign up to set email alerts
|

Short- and Mid-Term Loose Mix Conditioning Protocols for Asphalt Overlay Balanced Mix Design and Quality Control and Quality Acceptance

Abstract: Many aspects of balanced mix design (BMD) and performance-related quality control and quality acceptance (QC/QA) testing depend heavily on how the asphalt mixes are conditioned. There is, therefore, a critical need for practical loose mix conditioning protocols. The main objective of this study was to establish practical loose mix condition protocols for both the BMD and QC/QA phases. To develop these protocols, this paper reviewed the field performance and pavement lives of more than 200 test sections around … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The CT index was introduced based on the ideal cracking (IDEAL-CT) test method ( 12 ). Several studies have also reported that fracture energy, fracture work density, flexibility index values, and CT index values show high correlation with field results ( 1316 ). However, the simplicity, practicality, and repeatability of the IDEAL-CT have increased the popularity of this test over the past years ( 17 , 18 ).…”
mentioning
confidence: 80%
See 2 more Smart Citations
“…The CT index was introduced based on the ideal cracking (IDEAL-CT) test method ( 12 ). Several studies have also reported that fracture energy, fracture work density, flexibility index values, and CT index values show high correlation with field results ( 1316 ). However, the simplicity, practicality, and repeatability of the IDEAL-CT have increased the popularity of this test over the past years ( 17 , 18 ).…”
mentioning
confidence: 80%
“…Cracking test (CT) index values on load–displacement curve obtained from indirect tension/IDEAL-CT test method ( 15 ).…”
Section: Materials and Experimentsmentioning
confidence: 99%
See 1 more Smart Citation